PROSPECTS FOR THE DEVELOPMENT OF PHASED ANTENNA ARRAYS - A. P. Dzuba (Вестник Дагестанского государственного технического университета: Технические науки)
This article describes the main achievements in the development of phased antenna arrays (par) in the past decade. Provides an overview of the most famous systems based on the PAR and PAR based on MMIC technology - PAR in radar stations, PAR to control the laser and optical beams. The existing options for the design of the PAR:ferroelectric antenna array; plasma antenna with electronic scanning; reflective grating on 100-mm semiconductor wafers; wideband antenna arrays with aperture; antenna arrays with digital beam forming.